Textiloma Misdiagnosed as Paraspinal Abscess During the Period of COVID-19 Pandemic: Case Report - Yay, Murat Özcan; Sağıroğlu, Sinan; Turgut, Mehmet (Nepal Journal of Neuroscience, 2022)
Retained surgical sponge and consequent foreign body reaction is a well-documented complication. In the current literature, the phenomenon has many names such as textiloma, gossypiboma, gauzoma, and muslinoma. While it is one of the widely reported topics, only a few cases are reported by neurosurgeons. Herewith we present a case of textiloma in Turkey who had repeated surgical interventions at various hospitals during the COVID-19 pandemic, possibly due to breakdown of preventive measures against retention of surgical sponge.